Nisei linguists : Japanese Americans in the Military Intelligence Service during World War II - McNaughton, James C., 1952- (CMH pub, 2006)
Chronicles the establishment and achievements of U.S. Army Military Intelligence Service, the organization that trained and employed uniformed Japanese American linguists. Tells the story of second-generation Japanese Americans (Nisei) who served as interpreters and translators in World War 2. Describes how the War Department recruited soldiers from an ethnic minority and trained them in a secret school to use the Japanese language.